Capacities for the Risk Assessment of GMOs: Challenges to Build Sustainable Systems - Fernández Ríos, Danilo; Rubinstein, Clara; Vicién, Carmen (Frontiers in Bioengineering and Biotechnology, 2018)
The need for functional risk assessment bodies in general, and in the biosafety field in particular, demands continued efforts and commitment from regulatory agencies, if results that are sustainable in time are to be achieved. The lack of formal processes that ensure continuity in the application of state of the art scientific criteria, the high rotation in some cases or the lack of experienced professionals, in others, is a challenge to be addressed. Capacity building initiatives with different approaches and degrees of success have been implemented in many countries over the years, supported by diverse governmental and non-governmental organizations. This document summarizes some capacity building experiences in developing countries and concludes that risk assessors taking ownership and regulatory authorities fully committed to developing and retaining highly qualified bodies are a sine qua non to achieve sustainable systems. To this end, it is essential to implement “in-house” continuing education mechanisms supported by external experts and organizations, and inter-institutional cooperation. It has to be noted that these recommendations could only be realized if policy makers understand and appreciate the value of professional, independent regulatory bodies.